Penguatan Legalitas Usaha Berbasis Information Communication Technology (ICT) dalam Meningkatkan Pendapatan bagi UMKM - Maulana, Ahmad; Novalia, Nurkardina; Yuliani, Yuliani; Bashir, Abdul; Putri, Melisa Ariani (Penerbit Goodwood, 2023)
Purpose: The specific objective to be achieved in this service activity is to assist MSMEs in Burai Village in strengthening business legality, so as to increase competitiveness. Methodology/approach: The method used to implementing community service is service and assistance in meeting needs through service assistance and education. The series of methods used consisted of lectures, demonstrations, and mentoring. Results/findings: The implementation of community service activities in Burai Village received high enthusiasm from MSME players and involved support from the Village Head, community participation, enthusiasm of the participants, and assistance by the service team. On the other hand, the obstacles in this activity involve limited training time and distance, as well as obstacles in training follow-up. The impact of this activity involves increased knowledge about ICT-Based Business Legality, increased interest in entrepreneurship, and forum for marketing products through Digital Marketing. Nonetheless, there still challenges related to the lack of ICT usage and low business capital. Phase two mentoring highlighted legality issues and the lack of ICT utilization by MSMEs. Solutions include improving knowledge of business, SWOT analysis of MSME products, and optimization of digital marketing. It is also focus on appropriate digital media channels, maintaining customer loyalty, and innovative marketing strategies. Limitation: The implementation of mentoring requires limited time, causing the results achieved to be not optimal. The legality of MSMEs in Burai Village can be achieved if the mentoring process is carried out continuously. Contribution: The community service activities in Burai showed high enthusiasm and active support from MSME actors and related parties. Although successful in increasing knowledge and interest in entrepreneurship, challenges that need to be overcome involve limited use of ICT and low business capital.